The effect of non-visual working memory load on top-down modulation of visual processing - Rissman, Jesse (2009)
While a core function of the working memory (WM) system is the active maintenance of behaviorally relevant sensory representations, it is also critical that distracting stimuli are appropriately ignored. We used functional magnetic resonance imaging to examine the role of domain-general WM resources in the top-down attentional modulation of task-relevant and irrelevant visual representations. In our dual-task paradigm, each trial began with the auditory presentation of six random (high load) or sequentially-ordered (low load) digits. Next, two relevant visual stimuli (e.g., faces), presented amongst two temporally interspersed visual distractors (e.g., scenes), were to be encoded and maintained across a 7-sec delay interval, after which memory for the relevant images and digits was probed. When taxed by high load digit maintenance, participants exhibited impaired performance on the visual WM task and a selective failure to attenuate the neural processing of task-irrelevant scene stimuli. The over-processing of distractor scenes under high load was indexed by elevated encoding activity in a scene-selective region-of-interest relative to low load and passive viewing control conditions, as well as by improved long-term recognition memory for these items. In contrast, the load manipulation did not affect participants' ability to upregulate activity in this region when scenes were task-relevant. These results highlight the critical role of domain-general WM resources in the goal-directed regulation of distractor processing. Moreover, the consequences of increased WM load in young adults closely resemble the effects of cognitive aging on distractor filtering [Gazzaley et al., (2005) Nature Neuroscience 8, 1298-1300], suggesting the possibility of a common underlying mechanism.